Peningkatan Kinerja Guru Berbasis Budaya Sekolah dan Motivasi Kerja Guru - Intan Fauziyah; Abdul Komar (At- Ta'lim : Jurnal Pendidikan, 2020)
This study aims to determine the effect of school culture on teacher performance and the effect of teacher work motivation on teacher performance. This type of research is a qualitative research sourced from existing theories and previous research journals that are relevant to the variables in this study. The results showed that school culture had a positive effect on teacher performance, teacher work motivation had a positive effect on teacher performance.